2015
DOI: 10.18227/1982-8470ragro.v9i3.2571
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de estacas e uso de AIB na propagação vegetativa de fisális

Abstract: Resumo:Com o presente trabalho objetivou-se avaliar a propagação vegetativa de Physalis angulata L. utilizando-se diferentes tipos de estacas e concentrações de ácido 3-indolbutírico (AIB). Foram avaliadas mudas produzidas a partir de estacas coletadas em plantas matrizes na fase reprodutiva. O delineamento experimental foi em blocos ao acaso, em esquema fatorial 2 x 5, sendo os fatores constituídos por dois tipos de estacas (basal e mediana) e cinco concentrações de AIB (0, 400, 800, 1.200 e 1.600 mg L -1 ), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Root growth stimulation depends on several factors, mainly auxin concentration; an adequate supply of auxin can increase secondary root formation, generating seedlings with improved adaptive capacity and resistant to climatic variations (OLIVEIRA et al, 2015) The lowest root lengths of the cuttings were found when using the concentrations of 4.1, 4.5 and 4.1 g L -1 , with increases after these points, denoting that the use of IAA was beneficial to the cuttings, despite the low increases found (Figure 2A). The mean increase of 1.21 mm (9%) found when using the concentration of 10 g L -1 generated a greater adaptive advantage for the treated S. tuberosa cuttings.…”
Section: Resultsmentioning
confidence: 99%
“…Root growth stimulation depends on several factors, mainly auxin concentration; an adequate supply of auxin can increase secondary root formation, generating seedlings with improved adaptive capacity and resistant to climatic variations (OLIVEIRA et al, 2015) The lowest root lengths of the cuttings were found when using the concentrations of 4.1, 4.5 and 4.1 g L -1 , with increases after these points, denoting that the use of IAA was beneficial to the cuttings, despite the low increases found (Figure 2A). The mean increase of 1.21 mm (9%) found when using the concentration of 10 g L -1 generated a greater adaptive advantage for the treated S. tuberosa cuttings.…”
Section: Resultsmentioning
confidence: 99%
“…Physalis angulata L. (Solanaceae) is popularly known in the Amazon region as 'camapu'. It is an annual herbaceous plant with high pharmacological and agroindustrial potential (GUIMARÃES et al, 2010;OLIVEIRA et al, 2011) and propagated by seeds (OLIVEIRA et al, 2015). However, because it essentially is a wild species, with continuous flowering and irregular maturation, the occurrence of seeds with different levels of physiological quality (SANTIAGO et al, 2019), as well as low expression of their quality (CARVALHO et al, 2014), is common.…”
Section: Introductionmentioning
confidence: 99%